La frontera norte de México: Campo de desplazamiento, interacción y disputa - Everardo GARDUÑO (Frontera Norte, 2016)
A BSTR ACT Exclusion underlines the xenophobic edicts of the supposed mandate of the majority-predators of minorities-in daily acts of classism and racist jokes. These actions typically take place where dif ferent historicities enter into dispute as a result of displacement. This is the case in Baja California, where these expressions of exclusion are denied but not absent. This paper reveals how xenophobia and racism have been present throughout the history of this border, and have taken new forms today.